2019
DOI: 10.2196/15122
|View full text |Cite
|
Sign up to set email alerts
|

Examining Mobile Technologies to Support Older Adults With Dementia Through the Lens of Personhood and Human Needs: Scoping Review

Abstract: BackgroundWith the world’s rapidly growing older adult population, there is an increase in the number of people living with dementia. This growth leads to a strain on their caregivers and our health care system and to an increased attention on mitigating strain by using mobile technology to sustain the independence of people with dementia. However, less attention is given to whether these technologies meet the stated and unstated needs of people with dementia.ObjectiveThe aim of this study was to provide an ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 58 publications
0
42
0
Order By: Relevance
“…However, the low-interest levels in this study point to a barrier to technology adoption. Studies have found that learning to use new technologies can call an older adult’s attention to their diminishing memory and functioning [ 14 ], and it is possible that participants in this study were responding to such a recognition with denial of their need for assistive apps. It is clear from this study that simply demonstrating the functionality of assistive technologies is not enough to spark interest in their use, and that it may even turn potential consumers away if their use is perceived to be demeaning or to highlight impairments [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the low-interest levels in this study point to a barrier to technology adoption. Studies have found that learning to use new technologies can call an older adult’s attention to their diminishing memory and functioning [ 14 ], and it is possible that participants in this study were responding to such a recognition with denial of their need for assistive apps. It is clear from this study that simply demonstrating the functionality of assistive technologies is not enough to spark interest in their use, and that it may even turn potential consumers away if their use is perceived to be demeaning or to highlight impairments [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent literature review studied the possible barriers for older adults to use mobile technology [ 116 ], and another study evaluated the effects of technology-based self-monitoring that intend to improve health in middle-aged and older adults [ 117 ]. Other works on mobile technology have focused on specific aspects of older adult health, such as pain [ 17 ], dementia [ 26 ], or falls [ 22 ]. Unlike these studies, we present a systematic review of the literature on mobile health technology for older adults with a focus on self-reporting and data visualization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on mobile technology for health monitoring of older adults have focused on mobile applications to assess balance as a risk factor for falls [ 22 ], on health monitoring in the home [ 23 ], on tools for the support of diseases or health conditions of older adults such as pain [ 17 ], cardiovascular disease [ 24 ], mental problems [ 25 , 26 ]. This systematic review aimed to collate studies of mobile technology designed for the health support of older adults, focusing on the input/output aspects of the technologies, that is, identifying whether these technologies allow older adults to visualize monitored information and whether they can enter complementary data such as context or feelings.…”
Section: Introductionmentioning
confidence: 99%
“…This means that technologies must continue to monitor health and safety as primary needs, but it is necessary to support and maintain physical and mental capacity throughout the life-course by providing opportunities for leisure and social activities to facilitate inclusion, participation and thus reduce loneliness and social isolation [34]. Supporting higher level needs such as belonging, self-esteem, identity and self-actualization [35] is the aim of the next generation of technologies. Older adults are bearers of value for the design of technologies, and the beneficiaries of such systems.…”
Section: Discussionmentioning
confidence: 99%